2018
DOI: 10.1002/qj.3297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of algorithms for computing moist available potential energy

Abstract: Funding informationNERC; NE/L002566/1.Atmospheric moist available potential energy (MAPE) has traditionally been defined as the potential energy of a moist atmosphere relative to that of the adiabatically sorted reference state defining a global potential energy minimum. Although the Munkres algorithm can in principle find such a reference state exactly, its computational cost has prompted much interest in developing heuristic methods for computing MAPE in practice. Comparisons of the accuracy of such approxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…At each division, the pressure derivative of enthalpy is evaluated at the midpressure of the subdomain and used to order the parcels from top to bottom of the subdomain; the top and bottom halves are then assigned to new subdomains. The divide-and-conquer algorithm has been found to work well in practice (14,42), and in particular it gives a moist MAPE that is almost identical to that calculated using the exact Munkres algorithm for a similar case to the one considered here (14). We use divide and conquer rather than Munkres because divide and conquer is faster and more straightforward to adapt to calculate convective and nonconvective MAPE.…”
Section: Methodsmentioning
confidence: 99%
“…At each division, the pressure derivative of enthalpy is evaluated at the midpressure of the subdomain and used to order the parcels from top to bottom of the subdomain; the top and bottom halves are then assigned to new subdomains. The divide-and-conquer algorithm has been found to work well in practice (14,42), and in particular it gives a moist MAPE that is almost identical to that calculated using the exact Munkres algorithm for a similar case to the one considered here (14). We use divide and conquer rather than Munkres because divide and conquer is faster and more straightforward to adapt to calculate convective and nonconvective MAPE.…”
Section: Methodsmentioning
confidence: 99%
“…If the atmosphere is divided into parcels of equal mass, the changes in the atmosphere can be identified if the redistribution of these parcels is detected. The goal is to find the permutation of the parcels of the atmosphere with the least enthalpy (Harris and Tailleux, 2018). To be able to form parcels with equal mass, an coordinate (following Lorenz) was created that covers different areas starting from the pole, but the mass belonging to them is equal.…”
Section: The Exergy Concept In Atmospheric Energeticsmentioning
confidence: 99%
“…They tested these algorithms for more than 3700 soundings, and they found that best solution of the calculation of the exact is the Munkres algorithm, however, it has long runtime. When the approximation of the is enough Harris and Tailleux (2018) suggest the use of the divide-and-conquer method.…”
Section: The Exergy Concept In Atmospheric Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former case, z r should be defined either at the top or bottom of the domain depending on the buoyancy of the fluid parcel in the actual state (Tailleux 2013b). The latter case is rarely encountered in the ocean (Saenz et al 2015) but is commonplace in a moist atmosphere (Wong et al 2016;Harris & Tailleux 2018). How to select the solution in this case is still poorly understood, however.…”
Section: Available Energetics Of a Stratified Compressible Binary Fluidmentioning
confidence: 99%